Hepatectomy for liver metastasis from rectal cancer in a patient with mitochondrial disease. Issue 2 (5th February 2021) - Takei, Shogo; Homma, Yuki; Matsuyama, Ryusei; Endo, Itaru
Abstract : We herein report a woman who was suffering from type 1 diabetes and hearing impairment and whose mother had mitochondrial disease. Abdominal ultrasound identified a hepatic tumour, and a further examination led to the diagnosis of rectal cancer with synchronous multiple liver metastases. A genetic test led to the diagnosis of mitochondrial disease with a mitochondrial gene 3243A>G mutation. After neoadjuvant chemotherapy, we performed hepatectomy and low anterior resection in one stage. Hepatic vascular exclusion was not performed in order to prevent damage to hepatocytes due to liver ischaemia, and Ringer's lactate solution was not used to prevent lactic acidosis. The postoperative course was uneventful. Only one other case involving hepatectomy being performed in a patient with mitochondrial disease has been reported. Considering the extreme rarity of such cases and the importance of perioperative management, we report this case here.